GENDER EQUALITY VALUES IN PAI LEARNING MANAGEMENT IN STATE ELEMENTARY SCHOOL 200508 PADANGSIDIMPUAN - Silvia Anggraini Hsb; Anhar (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
This study aims to examine and analyze the implementation of gender equality values ​​in the management of Islamic Religious Education (PAI) learning at SD Negeri 200508 Padangsidimpuan. The main focus of the problem studied is how gender equality values ​​are implemented in PAI learning, whether there is a tendency for gender bias, and how teachers' efforts are to create a fair learning atmosphere for male and female students. The results of the study indicate that although there is no formal policy regarding gender equality in PAI learning at SD Negeri 200508 Padangsidimpuan, teachers have tried to create classes that are free from gender discrimination. Some of the steps implemented include equal time division, providing equal opportunities for all students to speak and ask questions, and teaching the importance of respecting each other without distinguishing between genders. However, several challenges, such as the existence of gender stereotypes that are still developing in society and limited educational facilities that support, affect the effectiveness of the implementation of gender equality principles. In conclusion, although teachers have tried to integrate gender equality values ​​in Islamic Religious Education learning, there is a need for increased training for teachers and improvements to the curriculum that are more responsive to gender issues to realize more inclusive learning at SD Negeri 200508 Padangsidimpuan.